The Influence of Social Networking Sites on the Well-Being of Young Adults in the Sultanate of Oman - Muthuraman, Subrahmanian; Al Haziazi, Mohammed; Al Balushi, Amani; Kumar. S, Arun (Journal of Ecohumanism, 2024)
The rapid increase in the use of social networking sites is expected to significantly impact the social system of Oman, particularly among its youth. This study aims to evaluate how social media affects the well-being of young adults in the Sultanate of Oman. Utilizing a survey research design, a structured questionnaire was developed, focusing on factors such as usage habits, engagement, enjoyment, as well as the positive, negative, and behavioural impacts associated with social networking sites as independent variables, and the overall influence of these platforms as the dependent variable. The study included 138 young adults aged 18 to 25 who identified themselves as social media users. Results demonstrated that all six independent variables contributed statistically significantly to the prediction of the dependent variable, with p < .05, indicating that the overall regression model is a good fit for the data. The findings underscore the need to promote the effective use of social media platforms. The study emphasizes the importance of community stakeholders providing moral support to educate young adults about the potential long-term negative impacts of social media usage. Additionally, young individuals are encouraged to perform self-assessments of their usage habits to identify early signs of technology addiction. As outlined in Oman Vision 2040, raising community awareness regarding health issues is crucial. The study specifically advocates for a greater understanding of the physical and mental health challenges that may result from excessive social media use and strongly recommends that young Omanis practice responsible use of social networking sites.